Antifungal efficiency and cytocompatibility of polymethyl methacrylate modified with zinc dimethacrylate - An, Jiali; Song, Yunpeng; Zhao, Jing; Xu, Baohua (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives Considering the high incidence rates of denture stomatitis, research that providing dental biomaterials with antifungal property are essential for clinical dentistry. The objectives of the present study were to investigate the effect of zinc dimethacrylate (ZDMA) modification on the antifungal and cytotoxic properties, as well as the variance in surface characteristics and other physicochemical properties of polymethyl methacrylate (PMMA) denture base resin. Methods PMMA with various mass fraction of ZDMA (1 wt%, 2.5 wt% and 5 wt%) were prepared for experimental groups, and unmodified PMMA for the control. Fourier-transform infrared spectroscopy (FTIR) was applied for characterization. Thermogravimetric analysis, atomic force microscopy and water contact angle were performed to investigate the thermal stability and surface characteristics (n=5). Antifungal capacities and cytocompatibility were evaluated with Candida albicans (C. albicans) and human oral fibroblasts (HGFs), respectively. Colony-forming unit counting, crystal violet assay, live/dead biofilm staining and scanning electron microscopy observation were performed to assess antifungal effects, and the detection of intracellular reactive oxygen species production was applied to explore the possible antimicrobial mechanism. Finally, the cytotoxicity of ZDMA modified PMMA resin was evaluated by the 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) assay and live/dead double staining. Results The FTIR analyses confirmed some variation in chemical bonding and physical blend of the composites. Incorporation of ZDMA significantly enhanced the thermal stability and hydrophilicity compared with unmodified PMMA (p < 0.05). The surface roughness increased with the addition of ZDMA while remained below the suggested threshold (≤ 0.2 µm). The antifungal activity significantly improved with ZDMA incorporation, and cytocompatibility assays indicated no obvious cytotoxicity on HGFs. Conclusions In the present study, the ZDMA mass fraction up to 5 wt% in PMMA performed better thermal stability, and an increase in surface roughness and hydrophilicity without enhancing microbial adhesion. Moreover, the ZDMA modified PMMA showed effective antifungal activity without inducing any cellular side effects.